Depot-specific characteristics of adipose tissue-derived stromal cells in thyroid-associated orbitopathy. Issue 8 (17th April 2018) - Wong, Janice Siu Chong; Chu, Wai Kit; Li, Benjamin Fuk-Loi; Pang, Chi-Pui; Chong, Kelvin Kam-lung
Abstract : Background: Thyroid-associated orbitopathy (TAO) causes inflammatory fibroproliferation of periocular connective tissues. We compared adipose tissue-derived stem/stromal cells (ADSCs) from three adipose depots of each patient with TAO on mesenchymal, myofibrogenic, adipogenic properties and associated hyaluronan (HA) synthesis. Methods: ADSCs were generated from periocular (eyelid, orbital) and subcutaneous (abdominal) adipose tissues of three patients with TAO. Mesenchymal markers were characterised by reverse transcription-PCR and immunofluorescent staining. A 3-week adipogenic induction was evaluated by Nile red staining and quantitative PCR (qPCR) of peroxisome proliferator-activated receptor (PPARγ), adiponectin and hyaluronan synthase (HAS)-2. A 7-day myofibrogenic induction was assayed by immunofluorescent staining and qPCR of α-smooth muscle actin (α-SMA). Results: ADSCs from all depots expressed similar levels of mesenchymal markers CD44, CD90 and CD105 (p=0.288, p=0.43 and p=0.837, respectively). After adipogenic induction, intracellular lipid increased for more than 32% and PPARγ mRNA showed more than twofold increase from all three depots. However, adiponectin and HAS-2 mRNA levels were significantly higher in the eyelid and orbital ADSCs than those from the subcutaneous ADSCs after induction (2.4×10 7, 3.9×10 6  folds vs below detection limit; 63.3-fold, 26.1-fold, vs 33% reduction, respectively; all p=0.002). Significantly more myofibroblasts and higher mRNA level of α-SMA were obtained from the orbital and eyelid compared with the subcutaneous ADSCs during myofibrogenic induction (80.2%, 70.6% vs 29.3%; 30.2-fold, 24.2-fold vs 1.7-fold, respectively; all p=0.002). Conclusion: ADSCs from different adipose depots of the same donors exhibited similar mesenchymal phenotypes but differed significantly in adipogenic, myofibrogenic potentials and associated HA synthesis. These depot-specific characteristics of ADSCs may contribute to site-specific adipose tissue involvement in TAO.